Atrial High-Rate Event Incidence and Predictors in Patients With Permanent Pacemaker Implantation - Chen, Jian Hua; Chen, Guo Yao; Zheng, Hong; Chen, Quan He; Fu, Fa Yuan; Zhang, Fei Long; Chen, Liang Long; Wang, Wei Wei (Frontiers in Cardiovascular Medicine, 2021)
Objective: The present study aims to investigate the incidence and predictors of atrial high-rate events (AHREs) in patients with permanent pacemaker implants. Methods: A total of 289 patients who were implanted with a dual-chamber pacemaker due to complete atrioventricular block or symptomatic sick sinus syndrome (SSS) and had no previous history of atrial fibrillation were included in the present study. AHREs are defined as events with an atrial frequency of ≥175 bpm and a duration of ≥5 min. The patients were divided into two groups according to whether or not AHREs were detected during the follow-up: group A (AHRE+, n = 91) and group N (AHRE−, n = 198). Results: During the 12-month follow-up period, AHREs were detected in 91 patients (31.5%). The multivariate Cox regression analysis revealed that patient age (odds ratio [OR] = 1.041; 95% confidence interval [CI], 1.018–1.064; and P < 0.001), pacemaker implantation due to symptomatic SSS (OR = 2.225; 95% CI, 1.227–4.036; and P = 0.008), and the percentage of atrial pacing after pacemaker implantation (OR = 1.010; 95% CI, 1.002–1.017; and P = 0.016) were independent AHRE predictors. Conclusion: The AHRE detection rate in patients with pacemaker implants was 31.5%. Patient age, pacemaker implantation due to symptomatic SSS, and the percentage of atrial pacing after pacemaker implantation were independent AHRE predictors.